Pengaruh Kombinasi Media Tanam dan Nutrisi Pada Sistem Hidroponik Wick Terhadap Pertumbuhan dan Hasil Tanaman Sawi Samhong (Brassica rapa L.) - Bram Felix; Bastaman Syah; Rika Yayu Agustini (Jurnal Ilmiah Wahana Pendidikan, 2023)
Samhong Mustard (Brassica rapa L.) is a vegetable commodity that has high prospects and has many benefits and nutritional content needed by the community. The purpose of this study was to analyze and obtain the best combination of planting media and nutrients in hydroponic wick system on the growth and yield of mustard greens (Brassica rapa L.). The research was conducted at Greenhouse , Bekasi City, West Java. The study was carried out for 3 months, from June 2022 to August 2022. This study was prepared using an experimental method using a single factor Randomized Block Design (RAK). There were 6 treatments with 4 replications, namely M1 (Zeolite + AB mix), M2 (Zeolite + Growmore), M3 (Pakis + AB mix), M4 (Pakis + Growmore), M5 (Rockwool + AB mix), M6 (Rockwool + AB mix), so there are 24 experimental plots. The results showed that the combination of planting media and nutrients had a significant effect on the growth and yield of mustard samhong, the combination of planting media and nutrients in the M5 (Rockwool + AB mix) treatment gave the most optimal results on the number of leaves, root length, and plant fresh weight and M1 (Zeolite + AB mix) treatment on plant height and leaf area